Penyingkiran Merkuri Dari Minyak Mentah Berat: Konversi Merkuri Ion ke Merkuri Metalik - Partono Adhi, Tri; Prabowo, Harris; Indarto, Antonius (Indonesian Journal of Chemical Research, 2020)
The presence of mercury in crude oil creates problems in oil processing in refineries, both in terms of operations and health. The previous removal process of mercury has not yet optimally removed mercury in the product, due to ionic and metallic mercury species. In this study, to obtain optimum results, the process of removal of mercury begins with the process of converting ionic (non-metallic) mercury into metallic mercury thermally in the liquid phase, followed by the transfer of metallic mercury to the gas phase by instant evaporation (flashing) and reinforced by gas stripping using internal gas cone from the evaporation of an instant. The results of the optimization of the process carried out can eliminate mercury with an efficiency of more than 95%.